Arthritis risk with immune checkpoint inhibitor therapy for cancer. Issue 3 (May 2019) - Pundole, Xerxes; Abdel-Wahab, Noha; Suarez-Almazor, Maria E.
Abstract : Purpose of review: This review summarizes the current evidence on inflammatory arthritis following cancer treatment with immune checkpoint inhibitors (ICI), and the effects of these therapies in patients with preexisting autoimmune arthritis. Recent findings: As the use of ICI for cancer therapy continues to expand, a myriad of immune-related adverse events (irAE) caused by these therapies are being recognized. Arthritis has been increasingly reported as a de novo irAE, presenting sometimes as a well defined disorder, such as rheumatoid arthritis or psoriatic arthritis, and in other occasions as undifferentiated monoarthritis, oligoarthritis, or polyarthritis. Remitting seronegative symmetric synovitis with pitting edema (RS3PE) and tenosynovitis have also been reported. Most published cases are reported as mild to moderate in severity. The most common treatment for arthritis has been systemic corticosteroids, although several patients have been treated with traditional disease-modifying antirheumatic drugs (DMARD), and a few, with biologic DMARD. Summary: Arthritis following ICI therapy is pleomorphic. Prompt identification and treatment are imperative to achieve optimal outcomes. Management should be multidisciplinary, including rheumatologists and oncologists, to ensure prompt symptomatic and functional management and continuation of cancer therapy as appropriate.